Generic tacrolimus in solid organ transplantation. (21st April 2014) - Taube, D.; Jones, G.; O'Beirne, J.; Wennberg, L.; Connor, A.; Rasmussen, A.; Backman, L.
Abstract The availability of a wide range of immunosuppressive therapies has revolutionized the management of patients who have undergone solid organ transplantation (SOT). However, the cost of immunosuppressive drugs remains high. This situation has led to the development of generic equivalents, which are similar in quality, safety, and efficacy to their approved innovator drugs. There are data available for three generic brands, tacrolimus (Intas), tacrolimus (PharOS), and tacrolimus (Sandoz). Bioequivalence has been demonstrated for generic tacrolimus (Sandoz) within a narrow therapeutic range to its innovator tacrolimus drug (Prograf) in both healthy volunteers and kidney transplant patients. Clinical experience with this generic tacrolimus formulation has also been established in both de novo and conversion patients who have undergone kidney and liver transplantation, as well as in conversion of other SOT patients, including lung and heart recipients.